So you’ve graduated college and need to test apps: What barriers might you face? - Shinzato, Flávio; Paiva, Débora Maria Barroso; Cagin, Maria Istela; Cafeo, Bruno B. P.; Fontão, Awdren (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS); 2021: Anais do XX Simpósio Brasileiro de Qualidade de Software, 2021)
With the increasing complexity and business surrounding mobile applications (apps), there is a growing demand from the industry for qualified test professionals. That’s why several universities have included app testing content in their curriculum. However, it is observed that novice app testers, despite being able to enter the market, may face barriers when performing activities related to testing. These barriers impact the tester’s experience and the quality of software testing. Although there are works that explore the barriers that newcomers face to participate/contribute in open-source communities or participate in projects that are already in progress, none of them address them from the perspective of app testing. Thus, this study advances in answering the following research question ”What are the barriers that novice testers face in the planning, execution, and analysis stages of the testing process?”. Through an opinion survey with 30 novice testers, six themes and 36 categories of barriers were synthesized, such as lack of knowledge about software measurement and about tools and technologies used in the test. The identification of these barriers can support professors in adapting and prioritizing content on Software Testing, especially in undergraduate courses. Furthermore, such contributions provide indications of the need for research on strategies to mitigate barriers.